Comparison between 100-g glucose tolerance test and two other screening tests for gestational diabetes: combined fasting glucose with risk factors and 50-g glucose tolerance test - Ayach, Wilson; Costa, Roberto Antonio Araújo; Calderon, Iracema de Mattos Paranhos; Rudge, Marilza Vieira Cunha (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Lack of consensus about which screening tests to use for gesta- tional diabetes mellitus (GDM) and difficulties in performing the gold-standard diagnostic test, the 100-g glucose tolerance test (100-g GTT), justify comparison with alternatives. The aim was to compare this with two other screening tests: combined fasting glucose with risk factors (FG+ RF) and 50-g GTT. DESIGN AND SETTING: Prospective longitudinal cohort study in the Hospital School of Universi- dade Federal de Mato Grosso do Sul. METHODS: The three tests were performed inde- pendently on 341 pregnant women. Sensitivity (S), specificity (Sp), positive (PPV) and negative (NPV) predictive values, positive (PLR) and nega- tive (NLR) likelihood ratios, and false-positive (FP) and false-negative (FR) rates obtained with FG + RF and 50-g GTT were compared with values from 100-g GTT. The average one-hour post-intake glucose levels (1hPG) with 50-g and 100-g were compared. Student’s t test was used in the statistical analysis. RESULTS: FG + RF led more pregnant women (53.9%) to diagnostic confirmation than did 50-g GTT (14.4%). The tests were equivalent for S (86.4 and 76.9%), PPV (98.7 and 98.9%), NLR (0.3 and 0.27) and FR (15.4 and 23.1%). Aver- age 1hPG values were similar: 50-g GTT = 106.8 mg/dl and 100-g GTT = 107.5 mg/dl. CONCLUSION: Diagnostic efficiency with sim- plicity, practicality and low cost make FG + RF more appropriate for screening for GDM. The equivalence of 1hPG allows a new, cheaper and less uncomfortable protocol to be proposed for screening and diagnosing GDM.